Allelopathic potential of Sapindus saponaria L. leaves in the control of weeds=Potencial alelopático de folhas de Sapindus saponaria L. no controle de plantas daninhas - Denise Garcia Santana; Sônia Cristina Juliano Gualtieri; Marli Aparecida Ranal; Patrícia Umeda Grisi (Acta Scientiarum: Agronomy, 2012)
The objective of this work was to evaluate the allelopathic potential of aqueous extracts of young and mature leaves from Sapindus saponaria on diaspore germination and seedling growth of barnyardgrass (Echinochloa crus-galli) and morningglory (Ipomoea grandifolia). The aqueous extract was prepared in a proportion of 100 g of dried, ground leaves dissolved in 1000 mL of distilled water, resulting in a 10% extract concentrate. Dilutions of this concentrate were made with distilled water to 7.5, 5.0 and 2.5%. In seedling growth tests, we compared the effect of these extracts with the herbicide nicosulfuron. Both extracts of mature and young leaves caused delays and reductions in diaspore germination and seedling length of barnyardgrass and morningglory, with the most intense effects observed at a concentration of 10%. The effects of the young leaf extract were more similar to those observed with the herbicide, demonstrating that leaf maturation stage of S. saponaria affects its inhibitory effects on the growth of other plants and that this species is effective in controlling weeds. O objetivo deste trabalho foi avaliar o potencial alelopático do extrato aquoso de folhas jovens e maduras de Sapindus saponaria (sabão-de-soldado) na germinação de diásporos e no crescimento de plântulas de capim-arroz (Echinochloa crus-galli) e corda-de-viola (Ipomoea grandifolia). O extrato aquoso foi preparado na proporção de 100 g de folhas secas e trituradas dissolvidas em 1000 mL de água destilada, produzindo-se o extrato considerado concentrado (10%). A partir deste, foram feitas diluições em água destilada para 7,5; 5,0 e 2,5%. No teste de crescimento de plântulas comparou-se o efeito desses extratos com o herbicida nicosulfuron. Os extratos de folhas maduras e jovens causaram atraso e redução na germinação dos diásporos e no comprimento das plântulas de capim-arroz e corda-de-viola, com efeitos mais intensos na concentração de 10%. No entanto, os resultados obtidos pelo extrato de folhas jovens foram mais similares ao efeito do herbicida, mostrando que o estágio de maturação da folha de S. saponaria interfere nos seus efeitos inibitórios e que esta espécie é eficiente no controle das plantas daninhas.